PENGARUH STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR BARANG KONSUMSI DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Luh Ayu Armita; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2020)
Thel purpose ofl thisl study was to determine thel effect ofl assetl structurel and company sizeonl capital structurel inl thel manufacturingl companies inl thel consumer goods industry sector whichwere listed onl thel Indonesial Stock Exchange inl 2016-2018. Thisl study uses external secondarydata, external secondary datal used inl thisl study is thel annual report ofl thel consumer goodsindustry sector which is onl thel Indonesial Stock Exchange inl 2016-2018 through thel websitewww.idx.co.id. inl thisl study thel samplingl usingl Purposive Samplingl techniques with certainconsiderations, where thel sample is 72 companies manufacturingl consumer goods industry sectorswhich are listed onl thel Indonesial Stock Exchange inl 2016-2018. Thel datal analysis technique usedis multiple linearl regression analysis. Based onl thel results ofl thel analysis found that assetlstructurel has a positive and significant effect onl capital structurel. Thisl shows that increasingl thelstructurel ofl assetls inl companies manufacturingl consumer goods, it tends to increase thel capitalstructurel. Thel size ofl thel company has no significant effect onl capital structurel. Thisl shows thatchanges inl company size (up or down) inl consumer goods manufacturingl companies, do not affectthel capital structurel.